FEATURES OF ACCOUNTING OF EXPENSES FOR CREATION AND DEVELOPMENT OF AN ENTERPRISE'S INTERNET SITE - A. A. Skornyakova (Russian Journal of Economics and Law)
The article views the difficulties in reflecting informative-communication products in accounting. The issue is important due to the lack of recommendations and instructions in normative documents allowing to arrange accounting of a site. The author gives a comparative characteristic of expenditures accounting at every stage by the Russian and international standards. The order of recognition and accounting of web-sites is presented by stages of their development, which allows to arrange accounting of informative-communication products.